Changes in serum alpha2 globulins in reticuloses. Issue 6 (November 1964) - Malpas, J. S.; Fairley, G. Hamilton
Abstract : The total concentrations of α2 globulin and two of its components, haptoglobin and caeruloplasmin, have been determined in the sera from 78 patients with primary malignant diseases of lympho-reticular tissue (reticuloses). The total α2 globulin fraction was significantly raised only in Hodgkin's disease. The serum haptoglobin was also significantly increased in Hodgkin's disease and some other reticuloses, including acute leukaemia, lymphosarcoma, and reticulum cell sarcoma. The serum level of caeruloplasmin was raised in all reticuloses. There was possibly some correlation between the rise in haptoglobin and caeruloplasmin concentrations and the total α2 globulin in Hodgkin's disease but this was not statistically significant. The significance of these results is discussed, and it is concluded that the increase in α2 globulin which occurs in Hodgkin's disease is due to an increase in several of its components and not to a single component.